2001
DOI: 10.1038/35092578
|View full text |Cite
|
Sign up to set email alerts
|

Mal (MyD88-adapter-like) is required for Toll-like receptor-4 signal transduction

Abstract: The recognition of microbial pathogens by the innate immune system involves Toll-like receptors (TLRs), which recognize pathogen-associated molecular patterns. Different TLRs recognize different pathogen-associated molecular patterns, with TLR-4 mediating the response to lipopolysaccharide from Gram-negative bacteria. All TLRs have a Toll/IL-1 receptor (TIR) domain, which is responsible for signal transduction. MyD88 is one such protein that contains a TIR domain. It acts as an adapter, being involved in TLR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
840
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,122 publications
(871 citation statements)
references
References 23 publications
17
840
0
7
Order By: Relevance
“…TLR4 signaling is relatively unique amongst TLRs in that the effector adaptors are one step removed from the receptor. For example, MyD88 recruitment to the receptor complex depends upon the TIR-domain containing adapter protein (TIRAP, also known as Mal) (Fitzgerald et al, 2001;Horng et al, 2002;Yamamoto et al, 2002). TLR2 also requires TIRAP to bridge MyD88 to the receptor; however it is believed that other MyD88-utilizing TLRs directly recruit MyD88.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…TLR4 signaling is relatively unique amongst TLRs in that the effector adaptors are one step removed from the receptor. For example, MyD88 recruitment to the receptor complex depends upon the TIR-domain containing adapter protein (TIRAP, also known as Mal) (Fitzgerald et al, 2001;Horng et al, 2002;Yamamoto et al, 2002). TLR2 also requires TIRAP to bridge MyD88 to the receptor; however it is believed that other MyD88-utilizing TLRs directly recruit MyD88.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…A second TIR domain-containing adaptor protein was identified by two independent groups, and was named MyD88 adaptor-like (Mal), also known as TIR domaincontaining adaptor protein (TIRAP) [16,17]. However, the generation of Mal (TIRAP) knockout mice showed that this adaptor is not responsible for Myd88-independent signalling and instead acts as a bridging adaptor between Myd88 and TLR4 and TLR2 [18,19].…”
Section: Myd88-dependent Signalling and Activation Of Nf-kbmentioning
confidence: 99%
“…71 ) and an MyD88-independent pathway involving the adapter protein TIRAP. 93,94 Activation of TLR4 by LPS leads to the induction of various host defense genes including pro-inflammatory cytokines such as IL1, IL6, IL8 and IL12, chemokines, costimulatory molecules (CD80 and CD86), MHC class II and NOS2 by APC cells. [95][96][97] Induction of CD80/CD86 and IL-12 by TLRs contributes to the initiation of adaptive immunity and the induction of TH1 effector responses.…”
Section: Tlr4mentioning
confidence: 99%